KOMUNIKASI INSTRUKSIONAL INSTRUKTUR PADA PROGRAM PEMBINAAN KELAS KERAJINAN TANGAN DI CABANG RUMAH TAHANAN NEGARA SELATPANJANG - Muhammad Hanafi; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The coaching program is one of the programs run by the State DetentionBranch Selatpanjang.. Instructor coaching program at Branch Selatpanjang usinginstructional communication in which there are several methods. One of theclasses in the coaching program at Rutan Selatpanjang branch is a handicraftclass that is able to utilize secondhand goods to be made into works such asminiature, souvenir and selling price. The community around even tourists areinterested to buy the craft. For now, the work of Batan Selatpanjang Branchresidents has come to areas such as Bengkalis, Dumai, Pekanbaru and evenabroad such as Singapore, Malaysia and South Korea. The purpose of thisresearch is to know the method, the media as well as the instructor instructionalcommunication barrier in the craft class guidance program at the Branch ofSelatpanjang Prison.This research uses qualitative research method. The research wasconducted at the Branch of Detention House of State Selatpanjang of TanjungMayat Village, Tebing Tinggi, Meranti Island district, Riau Province. Selection ofinfroman done by purposive technique. Data collection techniques used duringconducting research is by way of observation, interview and documentation.While the validity of data that researchers use is to extend the participation,triangulation and reference adequacy.The results showed that instructional instruction method used byinstructor in handicraft class of Branch Selatpanjang is using command method,practice/practice method, and question and answer method. While theinstructional communication media used by the instructor in the form of visualmedia such as drawings and whiteboard and media aids. Meanwhile, the barrierof instructional communication that occurred in the handicraft class of BranchSelatpanjang is in the form of obstacles to the technical media as well as theobstacle coming from the psychological communicant.Keywords: instructional communication, Coaching program, State detentionbranch of selatpanjang